Electrical Injuries: The Iceberg Phenomena - Krishna Manandhar (Society of Surgeons of Nepal, 2017)
Introduction: The deceptive nature of electrical injury is likened to an iceberg phenomenon. Whether the tissue is conductive or resistant both are injured due to electroporation and heat, respectively. The objective of the study is to evaluate the types and pattern of injuries and attempt to predict the chances of various types of injuries and highlight the iceberg phenomenon.